Halal Industry Dalam Peningkatan UMKM Masyarakat - Supandi, Ach. Faqih; Putri, Devina Yulinda; Umbar, Bastomi Dani; Hidayati, Hamdiah Nurul; Fawaid, Achmad (LAN TABUR : Jurnal Ekonomi Syariah, 2025)
Indonesia is a country that has enormous potential in the halal industry with the largest Muslim population, and is supported by UMKM which have an important part in the Indonesian economy with the largest workforce absorbing 99.9% of the total business actors in Indonesia. If the authority that Indonesia currently has is not immediately utilized, it will be left behind by other countries, because the development of the halal industry is also being followed by other countries even though the majority of these countries are not Muslim and the development of the halal industry continues to increase along with the increasing demand for halal products. . halal, which is a lifestyle. So it is very important to strengthen UMKM. This research uses a qualitative descriptive method and the data used in this research are secondary data sources obtained from research results, articles that discuss topics related to the research theme. The research results show that Indonesia has various potentials to become a market player in the world halal industry, requiring support from sharia-based UMKM that can be globally competitive. MSMEs are able to be globally competitive by strengthening halal certification, in accordance with UUD No. 33 of 2014, strengthening capital requires the contribution of sharia banking as well as strengthening the development of the quality of human resources, namely business actors so that they can always innovate and adapt to business developments and technological developments. Which is growing. Keywords: Halal Industry, Improvement of UMKM, Society